CO2 system in a Mediterranean frontal zone - Delgado, Olga; Estrada, Marta (Consejo Superior de Investigaciones Científicas (España), 1994)
14 páginas, 11 figuras, 2 tablas. [EN] Spatial and temporal variations of CO2 system parameters and O2 in the Catalan-Balearic Sea were studied during the PEP-86, FRONTS-86, PEP-87, and FRONTS-89, cruises. Complementary hydrographical data were also available. The zone of the Mediterranean Sea studied was a source of CO2, and O2 to the atmosphere during all the periods sampled (summer and early autumn). There was a close correlation between p CO2 and O2 vertical distributions, especially below the thermocline. A slower atmospheric exchange rate of CO2 compared to O2 is suggested to contribute to the frequently shallower O2 maximum. Minimum pCO2 low values have been associated with more productive areas and located closer to the Catalan front. The CO2 and O2 peaks were 10 to 20 m above the deep chlorophyll a (Chla) maximum. The more stratified the water column, the deeper the p CO2 minimum, and the O2 and Chla maxima. Calcite and aragonite oversaturation was found for the entire 2,000 m water column. Calcite saturation (Wcalcite) increased in the productive zones owing to photosynthetic CO2 removal. Differences in salinity standardised alkalinity (Alk35) between Western Mediterranean and North Atlantic waters were of the same magnitude as the variability among Western Mediterranean Alk35 data. In principal component analysis (PCA), the more conservative parameters of the CO2 system, total alkalinity (Alkt) and total dissolved inorganic carbon (S CO2), were frequently correlated with the first factor (40% of total variance), while the most metabolism-sensitive parameter, pCO2, was frequently correlated with the second factor (20% of total variance). Possibly, other processes besides the biological activity and gas transfer, are influencing the pCO2 and O2 vertical distributions. [ES] Se ha estudiado la variabilidad espacial y temporal de los diferentes parámetros del sistema CO2-carbonatos y del O2 en una zona frontal del Mar catalano-balear durante las campañas oceanográficas PEP-86, FRONTS-86, PEP-87, y ...